Emulsion Liquid Membrane Stability And Efficiency For Cadmium Removal Using Vegetable Oils - Buddin, Meor Muhammad Hafiz Shah (2015)
The application of Emulsion Liquid Membrane (ELM) in the extraction of cadmium ions was explored. ELM consists of internal and membrane phase that form the primary W/O (water-in-oil) emulsion which to be dispersed in the external phase. In promoting sustainable development, vegetable oil which is environmentally benign diluent was incorporated in the formulation of ELM, replacing the hazardous conventional petroleum derivatives diluent. The oil’s potentialities to be used as diluent in ELM was confirmed via a compatibility study with the carrier (Aliquat 336) and surfactant (Span 80). It is learned that corn oil showed a promising potential to be employed as diluent in ELM formulation. This study focused on the investigation of emulsion stability, namely membrane breakage and emulsion swelling. The effect of emulsion formulation parameters of the vegetable oil based ELM were investigated to obtain its best formulation, by taking into consideration emulsion stability as well as its effectiveness for cadmium removal from the external phase. The parameters involved are carrier and surfactant concentration, emulsification time as well as initial W/O volume ratio. These parameters were found to affect the stability and efficiency of the ELM developed. Data obtained shows that a stable emulsion and maximum cadmium removal efficiency were achieved with the usage of 3 wt% Aliquat 336, 3 wt% Span 80, W/O volume ratio of 0.33 and 15 mins of emulsification. At this condition, 0.05 % and 34.10 % membrane breakage and emulsion swelling was recorded, respectively. The prepared ELM was found to effectively remove 98.20% cadmium ions, comparable to the ones developed using petroleum derivatives as diluent.